Pelatihan Sistem Informasi Akuntansi Keuangan Berbasis Web Desa Tilote - Yulia Puspitasari Gobel (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The government as the office holder is expected to be able to direct all of its performance to become a good government, namely a clean government free from corruption, accountability and transparency. To realize this, a village government is needed that is able to account for all activities in the village. Initially, Tilote Village financial reports used SIMDA (Regional Information System) but since 2016 the Village has not used the SIMDA application system, because Reporting with the System has been transferred to Tilango sub-district, even though every village period must report all income and expenditures in the sub-district periodically, so that for village financial reporting using a manual system. so it is very doubtful if financial reporting can be reported accurately and on time. This problem is a major concern that requires a solution so that the hopes of village government officials in realizing the national good government program can be realized. Therefore, through community service activities by IAIN Sultan Amai Gorontalo lecturers, they offer a collaboration with partners, namely Tilote Village, Tilango District in realizing the expectations of the Village apparatus through WEB-based Village Financial Accounting Information System Training in realizing good governance and free from corruption. . WEB-based financial accounting information system training activities for village officials can realize village financial reporting that is accurate, reliable, timely, and accountable.